Highly enhancing the characteristics of immobilized thermostable β-glucosidase by Zn2+. (March 2018) - Shi, Xuejia; Zhao, Linguo; Pei, Jianjun; Ge, Lin; Wan, Pengwei; Wang, Zhenzhong; Xiao, Wei
Graphical abstract: Highlights: Effect of metal cations on β-glucosidase immobilized on NKA-9 was first studied. Metal cation Zn 2+ could activate the catalytic activity of immobilized Tpebgl3. The high thermostability of immobilized Tpebgl3 was greatly enhanced. The glucose tolerance of immobilized Tpebgl3 was greatly improved with Zn 2+ . Abstract: The thermostable GH3 β-glycosidase (Tpebgl3) from Thermotoga petrophila DSM 13995 was immobilized on macroporous resin NKA-9 modified with polyethylenimine (PEI) and glutaraldehyde (named NKA-9II). The properties of NKA-9II were as follows: the optimal conditions were the same as that of the free enzyme (pH 5.0; 90 °C), and the highest activity with cellobiose as the substrate approached 1.7 U/g; the thermostability, pH stability and glucose tolerance were greatly improved; the residual activity of NKA-9II was 68% of the initial activity at the end of 10 repeated cycles. Moreover, it was found that 2 mM Zn 2+ increased the relative activity of NKA-9II to 192% and 199% with cellobiose and p -nitrophenyl-β-d -glucopyranoside ( p NPG) as substrates, respectively. Meanwhile, Zn 2+ could greatly improve the reusability, high-temperature stability, and glucose tolerance of NKA-9II. In particular, 84% of the residual activity of NKA-9II with 2 mM Zn 2+ was retained, which was 21% higher than that with free metal ion after incubation at 85 °C for 7 h; when the glucose concentration was 400 mM, the free Tpebgl3 was completely inactivated, and NKA-9II with 2 mM Zn 2+ maintained 63% of its initial activity, which was 19.5% higher than the activity of NKA-9II in the absence of Zn 2+ .